Traditional Gender Stereotypes: A Critical Analysis of Visual Representation in Indonesian Senior High School EFL Textbooks - Kafania Nujhati; Joko Nurkamto (Jurnal Educative: Journal of Educational Studies, 2024)
This study explores the portrayal of gender roles, gender stereotypes, and gender activities in visual representations within English as a Foreign Language (EFL) textbooks used in Indonesian senior high schools. Using a Critical Feminist Discourse Analysis (CFDA) approach, investigates how these visual depictions promote or challenge existing gender stereotypes. The analysis focuses on textbooks used in Grades X and XI, identifying patterns in the representation of male and female characters. Key themes explored include the alignment of these portrayals with societal expectations of masculinity and femininity, especially in the contexts of professional roles and domestic roles. The findings reveal that, while traditional gender norms continue to dominate, there are emerging trends where gender roles are more diversified, particularly in the representation of women in career roles and men in caregiving or domestic settings. These results suggest that EFL textbooks gradually move toward more balanced gender representations, though traditional stereotypes remain prevalent. It emphasizes the need for a more inclusive and equitable approach to gender representation in educational materials